THE INFLUENCE OF ATTITUDE TOWARD GREEN PRODUCT ON GREEN PURCHASE BEHAVIOR IN E-COMMERCE - Golan Hasan; Andina Fasha; Reyhan Agustival I (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study aimed to identify factors that may influence green purchasing behaviour mediated by green purchasing intention. It used quantitative research designs, distributing questionnaires, and evaluating a specific population or sample. Its collection used a random sampling method, and the data were analyzed quantitatively. In this study, the population consisted of respondents who were aware of customers who previously purchased environmentally friendly, customer-friendly goods in Batam. It targeted 400 respondents. This study found that most of the hypotheses studied had a significant beneficial effect, except for a few that did not show a significant impact. In particular, attitudes towards green products, green purchasing behavior, perceived behavioral control, environmental concern, and green purchase intention had positive impacts. While the other two were not significantly related to each other. Attitudes towards green products, green purchase intention, and green purchase behaviour are associated with undesirable behaviours. Therefore, purchase intention does not mediate between attitude towards green products and green purchasing behaviour. Although environmental concern and product innovation may not always have the expected direct influence, the results generally imply that psychological and social factors play a significant role in shaping behaviour and intentions to purchase green products.